Gambaran Sopan Santun Mahasiswa STIKes Santa Elisabeth Medan Terhadap Ibu Asrama Tahun 2023 - Tri Karolina Laia; Febrina Br Sembiring; Daniel Imanuelta Gimting; Klara Selvriana Sinaga (Yayasan Literasi Sains Indonesia, 2023)
Politeness is an important aspect zin the dormitory environment, which involves respecting and communicating well with the dormitory mother as the dormitory administrator. This research aims to analyze the level of politeness shown by students towards dorm mothers at the STIKes SANTA ELISABETH MEDAN Student Dormitory. This research uses a descriptive design with a quantitative approach. In this study, there were 30 students as respondents in assessing students who were polite. In this research, researchers collected data using a questionnaire. The research was carried out in December 2023. Data was analyzed univariately. The research results showed that there were 27 respondents (90%) who assessed thatstudents had good manners, there were 2 respondents (6.6%) who assessed that’s students had sufficient manners and there was 1 respondent (3.3%) who assessed thatstudents who has poor manners. In this case, it is best for STIKes SANTA ELISABETH MEDAN students to maintain the polite behavior that has been carried out and try to improve the impolite behavior that is still being carried out.